Electrospun Mesoporous Composite CuO−Co3O4/N‐ TiO2 Nanofibers as Efficient Visible Light Photocatalysts. Issue 24 (22nd August 2017) - Pradhan, Amaresh C.; Senthamizhan, Anitha; Uyar, Tamer
Abstract: One‐dimensional mesoporous composite CuO−Co3 O4 /N ‐TiO2 nanofibers (CuCoNT NFs) have been fabricated by in situ sol−gel electrospinning technique. In our approach, both polyvinylpyrrolidone (PVP) and polyethylene glycol (PEG) are used as dual polymeric carrier matrix for the fabrication of electrospun CuCoNT NFs. PVP chains assist the electrospinning of the uniform composite nanofibers whereas PEG is responsible for mesoporosity which is confirmed by N2 sorption analyses. Along with CuCoNT NFs, other nanofiber samples (TiO2 NFs, N‐TiO2 NFs, CuO/N‐TiO2 NFs, Co3 O4 /N‐TiO2 NFs) have also been fabricated for comparative studies. The morphology and composition of the NFs have been confirmed by the HR‐TEM and XPS analyses. The red shifting of band gap energy from anatase TiO2 NFs to composite CuCoNT NFs (1.57 eV) is suggesting formation of visible light response. Oxygen vacancies in CuCoNT NFs, leads to lowering the e − − h + recombination. The lowering of photoluminescence spectrum and high photocurrent response in CuCoNT NFs makes CuO as low cost cocatalyst. The composite CuCoNT NFs is treated as an efficient photocatalyst for swift degradation of mixed dyes in visible light, an exemplary move. Exactly, 100% mixed dyes (30 mg/L) degradation is achieved at pH 10 in just 60 minutes. Abstract : Electrospun mesoporous composite CuO−Co3 O4 /N‐TiO2  nanofibers (NFs) are produced as the promising visible light photocatalyst for degradation of textile dyes and phenolic compounds in wastewater. Mesoporosity, NFs morphology, red shifting, oxygen vacancies and high photocurrent response are the key factors for the high photocatalytic degradation of such organicwastes in water.